The hydrogeological and contaminant transport properties of fractured Leda clay in eastern Ontario. - O'Shaughnessy, Vince. (University of Ottawa (Canada), 1993)
The objectives of the study were to investigate the hydraulic, geochemical and solute or contaminant transport properties of the upper fractured zone at four Leda clay deposits in Eastern Ontario. These four sites are known as NRC, Fallowfield, Renfrew and Casselman. Physical conditions and depth of fractures of the Leda subsoil was investigated with the use of boreholes and test pits. Piezometers were installed using a conventional auger method and the double-Shelby method developed at the University of Waterloo. Hydrogeological aspects of the upper twelve metres were analyzed using water level fluctuations and variation profiles, hydraulic head and conductivity profiles. A geochemistry analysis was made by measuring the major ions and tritium concentration distribution in groundwater samples obtained from piezometers. Laboratory tests were performed on five Leda clay samples to determine the effective diffusion coefficients and the retardation factors of the major ions. The results of the study indicated that the upper portion of Leda clay deposits within Eastern Ontario are fractured and hydraulically active. Fractured Leda clay deposits less than 12 metres in depth are highly questionable on their ability to protect any underlying aquifer from surficial or buried contaminants.
Keywords: Hydrology.